EFEKTIVITAS PELAKSANAAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI KELURAHAN MANISA KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Erfina Nurhayati Amir (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
Effectiveness of Property Tax collection in the village of Manisa Sidenreng Rappang. The background of this study is the lack of public participation in the payment of property tax. This research aims to determine the effectiveness of the implementation of property tax collection and to determine the factors that influence the effectiveness of the implementation of property tax collection in the village of Manisa Sidenreng Rappang. The population in this study is the head of the family in the Village Manisa using stratifid random sampling or random sampling. Data collection techniques used in this study is observation, interviews, questionnaires, and literature. The collected data is then used by means of qualitative data analysis techniques to the table percentage. The results of this study show that the effectiveness of the implementation of property tax collection in the village of Manisa Sidenreng Rappang categorized very effective with a percentage of 76.75%. Factors that influence the effectiveness of the implementation of property tax collection in the village of Manisa Sidenreng Rappang is the time factor with an average percentage of 71.25%, a factor precision and accuracy with an average percentage of 76.02%, and the factor ways and customs or style of service providers with an average percentage of 76.02%.